Evaluasi Pembelajaran Tematik dengan Penilaian Autentik di SDN Pasar Baru 1 Kota Tangerang - Ina Magdalena; Anggun Mila Banowati; Reni Safitri; Eka Nurwahyuningsih (Jurnal Halaqah, 2020)
This study aims to obtain comprehensive information about the evaluation of thematic learning by using authentic assessments at SDN Pasar Baru 1 Tangerang City. The findings are as follows: in the thematic learning evaluation activities with authentic assessment, the assessment uses the bloom taxonomy contained C1 to C6. In the implementation of authentic learning does not always run smoothly. There are several obstacles including the aspect of the teacher or instructor, there are still some who are less creative in the learning process. This makes the authentic assessment itself difficult to do. To overcome this, the teacher must be equipped with the ability to create more creative and diverse learning methods or media that can make learning more active, thus minimizing the obstacles in authentic assessment.